Early childhood environment, breastfeeding and the formation of preferences - Armin Falk; Fabian Kosse (Deutsches Institut für Wirtschaftsforschung (DIW), 2016)
This study provides insights on the role of early childhood family environment within the process of preference formation. We start by presenting evidence showing that breastfeeding duration is a valid measure of the quality of early childhood environment. In the main analysis, we then investigate how early childhood environment affects the formation of fundamental economic preferences such as time, risk, and social preferences. In a sample of preschool children we find that longer breastfeeding duration is associated with higher levels of patience and altruism as well as a lower willingness to take risk. Repeating the analysis on a sample of young adults indicates that the observed pattern is replicable and persists into adulthood. Importantly, in both data sets our findings are robust when controlling for cognitive ability and parental socio-economic status. We can further rule out that the results are purely driven by nutritional effects of breastfeeding. Altogether, our findings strongly suggest that early childhood environment as measured by breastfeeding duration systematically and persistently affects preference formation.
Keywords: C91; D64; D90; D81; J13; 330; time preferences; risk preferences; altruism; experiments with children; origins of preferences; childhood environment; breastfeeding